Kepatuhan Wajib Pajak Pasca Aturan PP No 23 Tahun 2018 pada UMKM Ekowisata Desa Singapadu - Krisna Yudha, Cokorda; Ratna Sari Dewi, Cok Istri (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p13, 2020)
This study aims to analyze the compliance of taxpayer post government regulation No. 23/2018 on Ecotourism MSEs in Singapadu Kaler and Singapadu Tengah Village. Based on data from the Directorate General of Taxes, the number of Final Tax payers is still very low compared to the total number of SMEs in Indonesia. Socialization and taxpayer knowledge are the main factors that affect taxpayer compliance given the large potential of MSEs in contributing to tax revenue. This study used qualitative research methods. The results showed the taxpayer compliance rate post government regulation No. 23/2018 in Singapadu village reached 85 percent. The lack of socialization lead to taxpayer knowledge about the regulation is not widely known by SMEs in the village. Keywords: Taxpayer Compliance; Government Regulation No. 23/2018; SMEs.